WOMEN'S LEADERSHIP IN ISLAM “Analysis of QS. Al-Nisa [4]: 34 Using Mubjadi's Qiraah Theory” - Fauzi, Ahmad; Khafidhoh, Khafidhoh; Dakir, Dakir; Syahid, Abdul (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
This study aims to explore the concept of female leadership in Islam through an analysis of QS. Al-Nisa [4]: 34 using the Qiraah Mubadalah theory. The methodology employed is qualitative descriptive with a library research approach that analyzes relevant literature and exegesis. The analysis is carried out through three main stages of the Qiraah Mubadalah theory: identifying the universal principles of Islam, interpreting the text inclusively, and applying the ideas in a context relevant to both men and women. The findings indicate that QS. Al-Nisa [4]: 34, often interpreted in a patriarchal manner, can be understood in a more egalitarian light, emphasizing that leadership roles are not exclusive to men but are also open to women with qualities such as responsibility, wisdom, and justice. This approach demonstrates that Islam supports gender equality in various aspects of life, including leadership in households, organizations, and society. The study concludes that leadership in Islam should be based on the values of justice and equality, transcending gender boundaries.